Association between toxoplasmosis and COVID-19 infection: A cross-sectional study - Ali Ehsan Shahbazi; Nastaran Barati; Eissa Soleymani; Pegah Khandan Del; Abolfazl Khandan Del; Nemat Azizi; Behjat ranjouri; Mehran Bakhtiari; Seyedmousa Motavallihaghi (Medical Laboratory Journal, 2023)
Background: COVID-19 is a respiratory disease pandemic and a major global health problem that can cause acute respiratory distress syndrome (ARDS). Previous studies have shown an inverse link between toxoplasmosis and COVID-19. This study aimed to evaluate the association between COVID-19 and toxoplasmosis infection. Methods: In this cross-sectional descriptive study, samples were taken from 360 patients, 50% of whom were men and 50% were women. Of the patients, 180 were determined to be COVID-19-positive by the ELISA kit, and 180 were in the control group. Some demographic characteristics, such as sex, age range, and occupation, were also recorded. Results: This study was conducted on 180 COVID-19-positive patients, of whom 26.7% were in the 16-30-year age group, 25.1% were self-employed, and 31.7% had anti-Toxoplasma gondii antibodies. Among the 180 control patients, 21.1% had antibodies for T. gondii. Of the 57 patients who were co-infected with both COVID-19 and toxoplasmosis, men had higher infection rates (63.2%) than women (36.8%). There was a significant relationship between co-infections with COVID-19 and toxoplasmosis with occupation, but not with age. Conclusion: The study found that people with toxoplasmosis infection have a 1.73 times higher risk of contracting COVID-19. The findings suggest that infectious agents could be a predisposing factor, possibly due to changes in cytokine levels.